PEMEROLEHAN DEIKSIS PEMEROLEHAN DEIKSIS PADA ANAK USIA 24 BULAN - Novita Indriyani (Universitas PGRI Adi Buana Surabaya, 2022)
Not only adults, toddlers also have the ability to use pronouns whose references are not fixed or often referred to as deixis. This study which aims to describe the acquisition of deixis in toddlers aged 24 months uses a descriptive qualitative approach. The result of the research shows that toddlers who are 24 months old still do not fully master deixis words. He only mastered some spatial deixis and some persona deixis, while for time deixis he had not mastered it at all. These results are expected to be a reference or consideration in building communication with toddlers.